Swiss sensibility : the culture of architecture in Switzerland - Roos, Anna (Birkhäuser, 2017)
"Contemporary architecture in Switzerland is influenced by Peter Zumthor and Herzog & de Meuron, recipients of the Swiss Pritzker Prize, as well as a number of other prominent architects. The book presents 25 buildings in Switzerland designed by 16 influential Swiss architects: The range covers high-density urban developments through to rural sites in the alpine environment, with examples of traditional craftsmanship and materials, and modern construction technology and engineering. Large-format photographs illustrate the buildings' proportions, materials, and details. Four authors analyze the Swiss building culture and its high architectural quality from an insider's and an outsider's point of view. In a detailed interview, Peter Zumthor explains his approach to architectural design."--Provided by publisher